Analysis of the Dynamic Source Routing Protocol on the Performance of File Transfer Protocol and Video Conference Services in the Mobile AdHoc Network Simulation - Cahyanto, Triawan Adi; Antoko, Rizky Dwi; Warisaji, Taufiq Timur; Santosa, Santosa; Rodianto, Rodianto (ILKOM Jurnal Ilmiah, 2023)
Current technological advancements make it easier for users to do their work effectively and efficiently, including the use of wireless networks to exchange data via File Transfer Protocol (FTP) and video conferencing services (VCS). A Mobile AdHoc Network (MANET) is a wireless network technology that applies a dynamic set of nodes. Data transmission on the MANET does not require the use of devices such as base stations. Because each node on the MANET can act as a router in determining the direction of the data sent, the number of nodes in the MANET will influence the quality of the data sent. Using the OPNET Modeler simulator, this paper shows how to assess the quality of FTP and VCS based on delay, jitter, and packet loss parameters. The simulation scenario employs five, fifteen, and thirty nodes with low, medium, and high traffic loads, using the Dynamic Source Routing (DSR) protocol. According to the measurement results, the FTP service with the bad category is the packet loss parameter in high traffic loads, which has the highest packet loss value of 56.6 percent with 15 nodes. In contrast, good results for VCS are only produced on the delay parameter. The jitter increases with the number of nodes, and it is 5 in this case. In all scenarios, the packet loss parameter yields poor results, with the highest packet loss value approaching 100%.